Nutrigenomic effects of Curculigo latifolia on type 2 diabetic model - Ishak, Nur Akmal; Ismail, Maznah (Institut Penyelidikan Perhutanan Malaysia, 2015)
The present study evaluated the anti-diabetic effects of Curculigo latifolia fruit:root. The hypoglycemic and hypolipidemic effects of C. latifolia fruit:root were investigated in high fat diet (HFD) with combination of low dose streptozotocin (STZ, 40 mg/kg body weight (b.w)) induced diabetic rats. C. latifolia fuit:root was orally administered once a day at 50, 100 and 200 mg/kg b.w for 30 days. Before and after treatments, plasma glucose, lipid and insulin were measured. The nutrigenomic effects of C. latifolia fruit:root extracts on genes involved in glucose and lipid metabolisms were further studied on glucose transporter (GLUT 4), leptin (LEP) and insulin receptor substrate 1 (IRS1) in adipose tissues. Results showed that 200 mg/kg b.w of C. latifolia fruit:root extracts significantly reduced blood glucose and plasma total cholesterol (TC), triglyceride (TG) and low density lipoprotein-cholesterol (LDL) levels. Meanwhile, insulin and high density lipoprotein-cholesterol (HDL) were increased. In addition, C. latifolia fruit:root extracts also increased the regulation of GLUT 4 (1 fold), Lep (3 fold) and IRS1 (2 fold) in adipose tissues. The results suggest that C. latifolia possess significant hypoglycemic and hypolipidemic effects. Hence, C. latifolia can be used as functional food or incorporated as a supplement in health-care food for the treatment of type 2 diabetic.